(untitled) (Моделювання, керування та інформаційні технології, 2020)
A modified method of numerical modeling for heterogeneous fluid dynamics processes with take of phase transitions will be presented. The method is based on the homogenization on cells and approximation of conservation laws for masses, momentums, and energies in integral and differential forms. The combination of Harlow’s particle-in-cell method, Belotserkovskii’s large particles method and Bakhvalov’s homogenization method is used for computing by the modified method simulation for processes with phase transitions.